(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The article examines the psycholinguistic mechanisms of maintaining professional neutrality and emotional resilience among interpreters engaged in English–Russian diplomatic simultaneous interpreting. The research highlights the cognitive and affective challenges interpreters face when processing emotionally charged diplomatic discourse, emphasizing strategies for regulating empathy, stress, and personal bias.